2015
DOI: 10.1136/bmjopen-2014-007235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcomes of multimorbidity in South Asia: a systematic review

Abstract: ObjectiveTo systematically review the studies of prevalence, patterns and consequences of multimorbidity reported from South Asia.DesignSystematic review.SettingSouth Asia.Data sourcesArticles were retrieved from two electronic databases (PubMed and Embase) and from the relevant references lists. Methodical data extraction according to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines was followed. English-language studies published between 2000 and March 2015 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
190
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(219 citation statements)
references
References 32 publications
26
190
3
Order By: Relevance
“…23 Several factors influence prevalence estimates among studies of multimorbidity, including differing geographic settings, recruitment methods, and data collection methods, and the operational definition of multimorbidity. 9,18,[24][25][26][27] In this study, we found that including risk factors has the largest impact on prevalence estimates. Compared to most diseases and symptoms, risk factors are generally based on objective, rather than subjective, measures; are easy to quantify; and are often collected as part of routine examinations (eg, blood pressure and BMI).…”
Section: Discussionmentioning
confidence: 59%
“…23 Several factors influence prevalence estimates among studies of multimorbidity, including differing geographic settings, recruitment methods, and data collection methods, and the operational definition of multimorbidity. 9,18,[24][25][26][27] In this study, we found that including risk factors has the largest impact on prevalence estimates. Compared to most diseases and symptoms, risk factors are generally based on objective, rather than subjective, measures; are easy to quantify; and are often collected as part of routine examinations (eg, blood pressure and BMI).…”
Section: Discussionmentioning
confidence: 59%
“…A more recent cross‐country comparison showed a high prevalence of multimorbidity in older people, suggesting that levels in LMIC were gradually approaching those of high‐income countries . Pati et al found the prevalence of multimorbidity in South Asia varied widely, mostly lower than those reported in high‐income countries, but most studies were based on small samples . We searched both Chinese and English language databases for studies of multimorbidity prevalence in China and found extremely divergent reports; for example, the proportion of older people reported with more than one chronic disease ranged from 6.4% to 90.5% …”
Section: Introductionmentioning
confidence: 99%
“…4 Pati et al found the prevalence of multimorbidity in South Asia varied widely, mostly lower than those reported in high-income countries, but most studies were based on small samples. 11 We searched both Chinese and English language databases for studies of multimorbidity prevalence in China and found extremely divergent reports; for example, the proportion of older people reported with more than one chronic disease ranged from 6.4% to 90.5%. 8,[12][13][14][15] The prevalence of multimorbidity in LMIC seems lower than that in high-income countries; 2,4,10,11 however, in both LMIC and high-income countries, a negative relationship exists between socioeconomic status and the prevalence of multimorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the health burden of chronic diseases for South America and the Caribbean, new research on multimorbidity in these areas of the world is warranted [29]. Although studies have shown that proper epidemiological characterization of multimorbidity is of great importance, it has been little explored, with few references in the literature for this region of the world.…”
Section: Introductionmentioning
confidence: 99%